Interactive display of molecular pathways and dynamics - Lee, Tat Loon. (2012)
As research progression of bioinformatics study expands, there is a growing demand to create platforms which can undertake roles to assist research analysis and network visualization. Interaction networks and biological data are getting more sophisticated in the gene expression profiles and expression data, thus it will be fruitful to have a software system that is able to query networks and visually integrate networks.